Analysing French Teacher Communities Producing Online Resources: New perspectives on teacher agency - Baron, Georges-Louis; Zablot, Solène (Canadian journal of learning and technology, 2025)
Online resources have become an important reality in education, accompanied by the phenomenon of the production, modification, and wide dissemination of educational resources by communities of teachers. This article explores the situation in France. First, we recall previous research on how teachers cooperate in order to create online resources. We distinguish between several types of collectives (captive communities, activist communities, proto-communities) and focus on their dynamics. Doing so implies considering the subjects as well as the instruments used and the social systems within which they evolve. Second, the issue of teacher agency relative to educational resources is analysed. In France, teachers are granted great freedom of pedagogical methods, a freedom not seen in all countries. Therefore, we analyse the activities of these collectives to understand how they view their activity and their role, specifically when using learning materials in class. An important related issue is the eagerness of administration to rely on evidence-based practice for orienting teacher action. We suggest that participatory research is a good investment for raising meaningful issues and proposing possible, short-term solutions. Les ressources en ligne sont devenues une réalité importante dans l'éducation, accompagnée d'un phénomène de production, de modification et de diffusion à grande échelle de ressources éducatives par des communautés d'enseignants. Cet article explore la situation en France. Tout d'abord, nous rappelons les recherches antérieures sur la façon dont les enseignants coopèrent pour créer des ressources en ligne. Nous distinguons plusieurs types de collectifs (communautés captives, communautés activistes, "proto-communautés") et nous nous concentrons sur leur dynamique. Cela implique de considérer non seulement les sujets, mais aussi les instruments que ces sujets utilisent et les systèmes sociaux au sein desquels ils évoluent. Deuxièmement, la question de l'agence des enseignants par rapport aux ressources éducatives est analysée. En France, les enseignants jouissent d'une grande liberté en matière de méthodes pédagogiques, ce qui n'est pas le cas dans tous les pays. Nous analysons donc les activités de ces collectifs pour comprendre comment ils perçoivent leur activité et leur rôle, en particulier lorsqu'ils utilisent des ressources pédagogiques en classe. Une question connexe importante est l'empressement des administrations à s'appuyer sur des bonnes pratiques fondées sur des preuves pour orienter l'action des enseignants. Nous suggérons que la recherche participative est un bon investissement pour soulever des questions significatives et proposer des solutions possibles (à court terme).